(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This study seeks to solve a standard problem that many researchers have long faced: the instability of the time series of variables, and how can follow-up statistical tests if this occurs, by applying the "Gregory-Hansen" methodology, which allows for structural breaks, which are the years that occurred It contains important changes in the direction of the variables as a result of certain events that affected the economy - which, if applied correctly, leads to obtaining stable time series with one or more intervals, as well as reaching statistically sound standard models. The previous methodology was applied to the time series of the public expenditures and total investment variables in Syria, by setting the first as an independent variable and the second as a dependent variable for a period of time that extends from the years before the economic crisis that Syria is going through until the crisis period itself, i.e. the period [2000-2017]. The study reached results, the most important of which are: Obtaining stable time series for public spending and total investment in Syria with structural intervals (years) defined by a statistical method. Also, there is a moral co-integration relationship between public spending and total investment, even during the years of the economic crisis in Syria.